Wzrost znaczenia instrumentów inwestycyjnych w polityce regionalnej Unii Europejskiej w perspektywie finansowej 2014-2020 - Małgorzata Michalewska-Pawlak (Ksiegarnia Akademicka Publishing, 2020)
The Increase of Significance Investment Instruments in Regional Policy of the European Union after 2014 The main objective of this paper is to analyse the increase of significance investment instruments in regional policy of the European Union after 2014. The reasons of this phenomenon have been pointed out in the context of the European Union structural funds. They refer to political interests, economic, social environmental challenges faced by the EU regions under conditions of limitation the EU expenditure on regional development financing. Solutions in the following areas: objectives, priorities and rules of intervention of the structural funds have been presented – those which have an investment dimension. Investment approach is going to be carried on in the next Multiannual Financial Framework after 2020. The paper has been elaborated based on using method of institutional analysis the key EU regional policy legal regulations and existing scientific literature.